Louisiana : The Collection and Buildings. - Bridgwater, Julia; Jensen, Knud W. (Humlebaek : Louisiana Museum of Modern Art, 1982)
Agger, Knud ; Albers, Josef ; Alechinsky, Pierre ; Alfelt, Else ; Andersen, Mogens ; Appel, Karel ; Arman ; Arp, Hans (Jean) ; AY-O ; Bacon, Francis ; Baselitz, Georg ; Battaglia, Carlo ; Beres, Jerzy ; Bertram, Helge ; Beuys, Joseph ; Bill, Max ; Bille, Ejler ; Buch, Hugo Arne ; Calder, Alexander ; Cane, Louis ; César ; Chadwick, Lynn ; Christo ; Christoffersen, Frede ; Corneille ; Couzijn, Wessel ; Dewasne, Jean ; Dibbets, Jan ; Dietman, Erik ; Dine, Jim ; Dubuffet, Jean ; Ernst, Max ; Errò ; Ferlov, Sonja ; Ferrara, Jackie ; Fischer, Adam ; Riverhead (New York) ; Fontana, Lucio ; Francis, Linda ; Francis, Sam ; Freddie, Wilhelm ; Gabo, Naum ; Gadegard, Poul ; Gernes, Poul ; Ghermandi, Quinto ; Giacometti, Alberto ; Giersing, Harald ; Girke, Raimund ; Graubner, Gotthard ; Green, Alan ; Groth, Jan ; Gudnason, Svavar ; Guerrero, José ; Hall, Nigel ; Hamilton, Richard ; Hansen, Lis Hooge ; Hansen, Svend Wiig ; Havsteen-Mikkelsen, Svend ; Heerup, Henry ; Hepworth, Barbara ; Herbin, Auguste ; Hodgkin, Howard ; Honegger, Gottfried ; Hoppe, Erik ; Hornung, Preben ; Hundertwasser ; Hunt, Bryan ; Ibsen, Immanuel ; Ipousteguy, Jean ; Isakson, Karl ; Jacobsen, Egill ; Jacobsen, Georg ; Jacobsen, Robert ; Jenney, Neil ; Jensen, Alfred ; Jensen, Soren Georg ; Jerichau, Jens Adolf ; Jorgensen, Mogens ; Jorn, Asger ; Judd, Donald ; Kadishman, Menashe ; Kandinsky, Wassily ; Kawaguchi, Tetsuo ; Kelly, Ellsworth ; Kienholz, Edward ; Kirkeby, Per ; Kivijarvi, Harry ; Klapheck, Konrad ; Klein, Yves ; Köpcke, Arthur ; Kudo, Tetsumi ; Kylberg, Carl ; Laurens, Henri ; Lavie, Raffie ; Lergaard, Niels ; Leth, Harald ; LeWitt, Sol ; Lichtenstein, Roy ; Lindström, Bengt ; Long, Richard ; Louis, Morris ; Lucebert ; Lundstrom, Vilhelm ; Mangold, Robert ; Manzoni, Piero ; etc.
biografie
Engels & Deens
boek